Pakistan Assessment of Civil Service Pensions - World Bank (World Bank, Washington, DC, 2020)
This report was prepared at the request in mid-2018 of the Secretaries of Finance for the Pakistan Federal Ministry of Finance, the Sindh Ministry of Finance and Punjab Ministry of Finance. Missions visited Pakistan in January and November 2018, the latter which included a week-long training program in the use of the Pensions Reform Options Simulation Toolkit (PROST). Policy discussions were held about reform options in January 2019 during a workshop on South Asia Civil Service Pension system in Bangkok, Thailand. The initial findings of the PROST projections were discussed with key counterparts in Islamabad, Karachi and Lahore in October, 2019. This report evaluates the current civil service pension scheme and suggests options to consider for pension policy and parameter reforms to improve sustainability, equity and predictability. Actuarial projections have been employed for the civil servant schemes for the Federal civil servants, and for civil servants in Punjab and Sindh. We have not modeled the schemes for other provinces, for Autonomous Authorities or for Uniformed Forces. This report is organized as follows: section two reviews the design, parameters and coverage of the civil servant pension schemes in Pakistan; section three evaluates the key challenges presented in these schemes; section four suggests options for parametric and structural reforms; and section five concludes.